Development and validation of a volunteer nostalgia scale: assessing measurement invariance across cultures and types of volunteering. Issue 16 (18th August 2022) - Cho, Heetae; Lee, Hyun-Woo
ABSTRACT : Volunteers' nostalgia, which is a multifaceted concept, has not been fully explored, while the concept of nostalgia is receiving increased attention in many fields for its role and effect on individuals' behaviour. In this study, the authors applied multigroup invariance tests to develop a volunteer nostalgia scale. This study consists of three phases. In the first phase, 180 participants with previous nostalgic volunteer experience were recruited in Singapore for the pilot study. In the second phase, data were collected from the United States ( n  = 201) and Singapore ( n  =   203) for the assessment of psychometric properties and cross-cultural validation of the scale. In the third phase, invariance tests were conducted to compare tourism event volunteers with volunteers for non-tourism sectors ( n  =   420). Results showed consistency between the data, indicating the robustness of the scale, which can be a useful tool in future research involving nostalgia.